Phenotypes of primary sclerosing cholangitis in children - M.B. Dyba; V.S. Berezenko (Gastroenterologìa)
Background. Primary sclerosing cholangitis (PSC) in children is a rare chronic immune-mediated disease of the biliary tract, which, unlike in adults, has a less aggressive course with damage to the intrahepatic bile ducts and is combined with autoimmune hepatitis, creating a special clinical phenotype of PSC, autoimmune sclerosing cholangitis (ASC). Although immunosuppressive therapy is effective in controlling autoimmune inflammation, it does not inhibit the progression of fibrotic changes around the bile ducts, which, unfortunately, leads to the formation of biliary cirrhosis of the liver. Research aimed at studying the clinical course of PSC in children and improving early diagnosis is relevant, especially given the limited access to modern diagnostic methods, such as magnetic resonance cholangiopancreatography, the need for invasive studies, and the lack of standardized diagnostic criteria adapted to childhood, which complicates the diagnosis and treatment of these patients. Objective: to investigate the clinical features of primary sclerosing cholangitis in children and adolescents depending on disease phenotype with the aim of developing individualized treatment approaches. Materials and methods. Retrospective and prospective analysis of the clinical course of primary sclerosing cholangitis in children and adolescents who were treated and followed at the Department of Pediatric Hepatology from 2016 to 2024 was conducted. The study included 68 children (62 % boys and 38 % girls) with PSC aged 3 to 18 years (mean age at diagnosis was (11.0 ± 3.9) years). Of these, 38 patients (56 %) had autoimmune sclerosing cholangitis, and 30 (44 %) had isolated PSC without clinical or histological signs of autoimmune hepatitis. Results. At disease onset, 40 % of children with PSC had liver fibrosis graded F3-F4 on METAVIR, with 24 % showing cirrhosis. The most common phenotype in children with PSC was a mixed one involving both large and small bile ducts (63 %). PSC with large bile duct involvement alone was observed in 11 % of cases, 70 % of these children were diagnosed with cirrhosis. Small duct involvement alone was present in 26 % of cases, with cirrhosis in 12.5 % (p = 0.01). Inflammatory bowel disease (IBD) was diagnosed in 84 % of children with PSC: 32 % had ulcerative colitis, 38 % had indeterminate IBD, and 16 % had Crohn’s disease. Pancolitis occurred in 56 % of cases, while 19 % of patients had histological signs of IBD without clinical or endoscopic manifestations. Asymptomatic IBD was diagnosed in 58 % of cases. The clinical course of ASC differed from isolated PSC with significantly higher rates of anemia (47 vs. 27 %, p = 0.03), elevated serum IgG levels (23.9 vs. 12.5 g/l, р < 0.01), and higher levels of alanine aminotransferase, aspartate aminotransferase, total bilirubin (p < 0.01 for all), non-invasive fibrosis markers (APRI, FIB-4, 2D-SWE) at onset (p < 0.01; p = 0.01; p = 0.04, respectively). Liver fibrosis F3-F4 on METAVIR was more frequently diagnosed in ASC group than in patients with isolated PSC (73 vs. 40 %, p = 0.06). Large bile duct involvement alone was found only in isolated PSC (p < 0.0009). No differences were observed between ASC and isolated PSC in terms of IBD phenotype. Conclusions. PSC in children is represented by 2 phenotypes (ASC and isolated PSC) that occur with almost equal frequency. ASC and isolated PSC have similar phenotypes of biliary and intestinal lesions, however, they differ in terms of clinical course and therapeutic approaches. Involvement of the large bile duct alone in children with PSC is associated with rapid formation of liver fibrosis and cirrhosis. PSC phenotype with involvement of small bile ducts alone has a favorable course in children. Most children with PSC exhibit the PSC-IBD phenotype. Active diagnostic search for biliary and intestinal lesions in children with PSC will facilitate the development of effective personalized approaches to treatment and monitoring, thereby improving disease prognosis.